Depression mediates the association between lipid accumulation products and overactive bladder - Caijuan Huang; Ying Xu; Yibing Guan; Jingjing Liu; Haiping Yang (Scientific Reports)
Abstract The relationship between lipid accumulation products (LAP) and overactive bladder (OAB) has not been explored. This study aims to investigate the relationship between LAP and OAB and the mediating role of depression. Data from seven cycles of the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018 were used to analyze the relationship between LAP and OAB. The association between LAP and OAB was estimated using multivariable logistic regression models, and the dose-response relationship was estimated using restricted cubic splines (RCS). In addition, subgroup analysis was also performed. Moreover, important factors associated with OAB were identified by Random Forest (RF). Finally, the extent to which depression mediates the association between LAP and OAB was investigated. A total of 13,861 participants with an average age of 49.65 years were enrolled, including 6,869 females (50%), of which 2,739 were diagnosed with OAB. The age-adjusted prevalence of OAB gradually increased among the quartile groups of LAP. In the fully adjusted model, there was a significant positive association between Ln(LAP) and OAB [adjusted odds ratio (AOR): 1.158, 95% CI: 1.073–1.251, P < 0.001]. In the categorical model of LAP, compared with the lowest quartile group of LAP, the prevalence of OAB in the highest quartile group significantly increased after adjustment (AOR: 1.320, 95% CI: 1.105–1.578, P = 0.002). The trend test (P for trend < 0.001) and RCS (P for nonlinearity = 0.196) consistently indicated a linear relationship between LAP and OAB. Subgroup analysis suggested that female gender was an important interaction variable. RF indicated that LAP was the most important factor associated with OAB other than age. Furthermore, in the mediation analysis, depression explained approximately 10% of the association between LAP and OAB. Our research results indicate that there is a linear positive association between LAP and OAB, and there is a significant interaction between gender and LAP. In addition, depression is an important intermediate factor in the association between LAP and OAB.